2004
DOI: 10.1038/ng1324
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive joint influence of epistasis and plasticity on mutational effects in Escherichia coli

Abstract: The effects of mutations on phenotype and fitness may depend on the environment (phenotypic plasticity), other mutations (genetic epistasis) or both. Here we examine the fitness effects of 18 random insertion mutations in E. coli in two resource environments and five genetic backgrounds. We tested each mutation for plasticity and epistasis by comparing its fitness effects across these ecological and genetic contexts. Some mutations had no measurable effect in any of these contexts. None of the mutations had ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 26 publications
4
96
1
Order By: Relevance
“…This is precisely what the fluctuation parameter measures in the generic case: the fitness changes at a given site driven by external causes or by the coupled evolution of the remainder of the genome. Fitness interactions changing the direction of selection for substitutions at a given site, so-called sign epistasis (41), occur in a number of observations and models of protein, RNA, and regulatory evolution (19,40,(42)(43)(44)(45)(46). Thus, the higher values of in UTRs, intronic and intergenic DNA shown in Table 1 are in accordance with the expected ubiquity of sign epistasis in regulatory sequences (13,19).…”
Section: Resultsmentioning
confidence: 65%
“…This is precisely what the fluctuation parameter measures in the generic case: the fitness changes at a given site driven by external causes or by the coupled evolution of the remainder of the genome. Fitness interactions changing the direction of selection for substitutions at a given site, so-called sign epistasis (41), occur in a number of observations and models of protein, RNA, and regulatory evolution (19,40,(42)(43)(44)(45)(46). Thus, the higher values of in UTRs, intronic and intergenic DNA shown in Table 1 are in accordance with the expected ubiquity of sign epistasis in regulatory sequences (13,19).…”
Section: Resultsmentioning
confidence: 65%
“…Experimentally, the strength and sign of epistasis have been measured across a variety of systems Kouyos et al 2007;Trindade et al 2009;Silva et al 2011), reporting all forms of epistasis. Moreover, several studies have investigated the influence of the environment on the epistatic interactions between mutations, finding that both the strength and the sign of epistasis can change as the environment changes (Remold and Lenski 2004; Lalic and Elena 2012;De Vos et al 2013;Flynn et al 2013). This shows that for a comprehensive picture of the role of epistasis on adaptation upon environmental change, all possible fitness schemes in both environments need to be studied.…”
Section: The Role Of Epistasismentioning
confidence: 99%
“…Importantly, although pathway A and B have distinct functional roles, they have the capacity to compensate each other's loss in Environment III. Hartl, 2002;Remold and Lenski, 2004); hence, natural selection to promote survival under a large variety of environments might indirectly increase mutational resilience. As a further support, it has been recently demonstrated that a large fraction of the compensating gene pairs in cellular networks bears distinct functional roles and are not redundant under all conditions (Harrison et al, 2007;Ihmels et al, 2007), suggesting that these genes are unlikely to be maintained by direct selection for mutational robustness.…”
Section: Robustness Against Gene Deletions Appears To Be a By-productmentioning
confidence: 99%